ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS USAHATANI PADI SAWAH DI KECAMATAN BATHIN III ULU KABUPATEN BUNGO - Hidayat, Ahmad; Damayanti, Yusma; Utami Lestari, Sri (Universitas Jambi, 2026)
This study used primary data obtained from 83 farmer respondents through interviews using a questionnaire. Data analysis was performed using the Cobb-Douglas production function model in natural logarithm form and processed using SPSS 27 software. The results showed that the average land area cultivated by farmers was 0.4 ha, with labor usage of 59.83 HOK/ha/MT, seed application of approximately 23.94 kg/ha/MT, NPK fertilizer application of approximately 201 kg/ha/MT, urea application of approximately 136 kg/ha/MT, and pesticide application of 88.87 ml/ha/MT. Farmers generally planted twice a year using a tiled planting system. The analysis results showed that the five variables in the model explained 85.9% of the variation in rice farming productivity (R2 = 0.859). Partially, NPK and Urea fertilizer variables had a positive and significant effect, while labor (HOK/ha/MT) had a negative and significant effect. Seed and pesticide variables did not have a statistically significant effect. These findings indicate that labor efficiency and the application of appropriate cultivation techniques are key to increasing rice farming productivity in Bathin III Ulu District, Bungo Regency. These findings indicate that the government needs to focus its policies on ensuring the proper provision and distribution oversight of subsidized fertilizers so that they effectively meet farmers' needs, while also enhancing extension programs regarding balanced fertilization, labor efficiency, and the adoption of good cultivation practices. Given that the majority of farmers already use high-yielding seeds, extension efforts should aim to sustain consistent usage alongside appropriate cultivation techniques. Furthermore, training and guidance on proper pesticide application must be strengthened to ensure that farmers not only increase input quantities but also pay attention to the quality and effectiveness of their use.